Literature Review : The Effect of Service Quality on Patient Satisfaction During the Covid-19 Pandemic Based on SRVQUAL Scale - Ascobat Gani; Dian Agnesa Sembiring; Riki Yedija Lumban Tobing (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The Covid-19 pandemic has forced hospital management need to take quick action in overcoming the crisis while maintaining and improving the relationships with the customers in order to remain satisfied with the quality of service in hospitals. The study’s goal was to use SRVQUAL Scale to describe the impact of service quality on patient satisfaction during the Covid-19 (reliability, tangibles, empathy, assurance, responsiveness). This paper  was a literature review sourced from Pubmed and ProQuest articles with keywords ("quality of service" or "service quality" or "quality of health services") AND ("patient satisfaction" OR "patient perspective" OR "patient experience") AND ("covid" OR "pandemic"). Six publications were found to meet the inclusion criteria following a review utilizing the PRISMA flow chart. The findings shown that in the Covid-19 pandemic era, all aspects of service quality (reliability, tangibles, empathy, assurance, responsiveness) have positve and significant impact on patient satisfaction. The study’s findings can helphospital management understand the issues that must be taken into account in order for patients to continue to be happy with the standard of care provided by hospitals, particularly during Covid-19 pandemic.